Strategic concept paper for bioeconomy in Poland: executive summary [version 1; peer review: 3 approved, 1 approved with reservations] - Magdalena Borzęcka; Mariusz Maciejczak; Stelios Rozakis; Justyna Cieślikowska; Jerzy Kozyra; Piotr Jurga; Paweł Chmieliński (Open Research Europe, 2023)
The main objective of the proposed approach is to accelerate the transition of the bioeconomy towards a knowledge-based sustainable system, covering key biobased sectors strongly linked to agriculture in Poland, in line with the European Green Deal. The proposed model of a bioeconomy development strategy, with a special focus on agriculture, is based on two pillars: (1) strengthening traditional, relevant (in terms of economic indicators) sectors of the economy and improving their ‘sustainability’ by implementing the proposed transformation pathways; and (2) developing economic activities or ‘niche or novel sectors’ that are prospective accelerators of change in the face of climate challenge, and ensuring their upscaling. This approach forms the basis for policy planning at national and regional level in these European Union (EU) countries, where bioeconomy development strategies have been initiated through dialogue between science, administration and industry stakeholders. The strategic actions we propose are grouped in three areas; (1) Market intervention mainly by introducing sustainability criteria for the national production system; (2) Research, innovation and education that significantly strengthen the relationship between business and science and educational activities in the field of sustainability and climate change, and (3) Governance and policy actions to enforce the relationship between the main sub-sectors of bioeconomy and niche sectors in frame of bio-economy strategy or action plan that will profits by added value of products from bioeconomy sectors and increasing number of newly created jobs.